Empirical validation of affect, behavior, and cognition as distinct components of attitude - Breckler, S J (Journal of personality and social psychology, 1984)
A prevalent model of attitude structure specifies three components: affect, behavior, and cognition. The validity of this tripartite model was evaluated. Five conditions needed for properly testing the three-component distinction were identified. Two new studies were then designed to validate the tripartite model. A consideration of the tripartite model's theoretical basis indicated that the most important validating conditions are (a) the use of nonverbal, in addition to verbal, measures of affect and behavior, and (b) the physical presence of the attitude object. Study 1, in which subjects' attitudes toward snakes were examined, indicated very strong support for this tripartite model: The model was statistically acceptable, its relative fit was very good, and the intercomponent correlations were moderate (.38 less than r less than .71). Study 2 was a verbal report analogue of Study 1. Results from Study 2 indicated that higher intercomponent correlations occurred when attitude measures derived solely from verbal reports and when the attitude object was not physically present.